Officers and Committees of the Petroleum Division (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
M. AlbERtson, Chairman. Production Engineer, Shell Petroleum Corporation, Houston, Texas. R. P. McLaughlin, Associate Chairman. General Manager, Burnham Exploration Co., Los Angeles, Calif. Eugene A. Stephenson, Secretary-Treasurer. Professor of Petroleum Engineermg, Missouri School of Mines and Metallurgy, Rolla, Mo. Ezecutive Commillee M. Albertson, Chairman. C. E. Beecher, Empire Oil & Refining Co., Bartlesville, Okla. L. L. Foley, Petroleum Engineer and Geologist, Tulsa, Okla. R. B. Kelly, Division Manager, Pure Oil Co., Fort Worth, Texas. Hallan N. Marsh, Production Engineer, General Petroleum Corporation of California, Los Angeles, Calif. R. E. Somers, Geologist, The Gulf Companies, Pittsburgh, Pa. Production Engineering T. V. Moore, Vice-chairman. Charge Production Research Division, Technical Service and Development Dept., Humble Oil & Refining Co., Houston, Texas. Joseph Chalmers. De Bataafsche Pet. Maatschappij, The Hague, Netherlands. M. L. Haider, Petroleum Engineer, Carter Oil Co., Tulsa, Okla. Emile HUGUENIN, Deputy State Oil and Gas Supervisor, Los Angeles, Calif. Carl E. Reistle, Jr., Petroleum Engineering Dept. Humble Oil & Refining CO., Houston. Texas. Produclion J. Terry DUCE, Vice-chairman. Geologist, The Texas Company, New York, N. Y. Basil B. Zavoico, Associate Vice-chairman. Consulting Geologist, Houston, Texas. Engineering Research R. L. Huntington, Vice-chairman. Associate Professor, Petroleum Engineering, University of Oklahoma, Norman Okla. Economics Sidney A. Swensrud, Vice-chairman. Assistant to the President, Standard Oil CO., Cleveland, Ohio. Refinery Engineering Walter Miller, Vice-chairman. Vice-president, Continental Oil Co., Ponca City, Okla.